Research progress on macroporous hydrogel scaffolds - LU Zhengkuan; LIN Shuxian; SU Jiansheng (Kouqiang hemian waike zazhi)
As a tissue engineering restorative material, hydrogel possesses outstanding biocompatibility, degradability and plasticity. Due to the lack of appropriate pore characteristics, the proliferation, migration and angiogenesis of cells inside and outside the gel are limited, which seriously affect the results of tissue engineering. Therefore, the preparation of macroporous structure has become a research focus on modification of hydrogel. In this paper, the effect of pore characteristics on biological behavior of scaffolds and the prepared methods of macroporous structure in recent years are reviewed.